Terjemahan sebagai Arena Gender: Analisis Bias Patriarkal dalam Pilihan Leksikal Al-Quran Terjemahan Kemenag RI Edisi 2019 - Sriana; Yufridal Fitri Nursalam (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study reveals ideological inconsistencies in the 2019 edition of the Qur’an translation published by the Indonesian Ministry of Religious Affairs (MoRA), which claims to embody the values of “religious moderation” yet continues to reproduce patriarchal bias in verses related to women. Employing a comparative qualitative design through Fairclough’s Critical Discourse Analysis and lexical comparison, the research contrasts three official Indonesian translations (1971, 2002, 2019) with two feminist translations by Amina Wadud and Laleh Bakhtiar. The analysis focuses on four key verses—QS 4:34, 2:228, 33:59, and 24:31. Findings indicate that MoRA’s translation consistently opts for the most patriarchal interpretations of Arabic words with broad semantic ranges: qawwāmūn as “leaders” rather than “protectors,” waḍribūhunna as “beat them” instead of “separate from them,” and darajah as “superiority” rather than “greater responsibility.” Moreover, while the 2019 edition revised politically sensitive verses such as QS 5:51 (“leaders” “protectors”) following socio-political controversy, it left gender-related verses unchanged. The study concludes that MoRA’s notion of “religious moderation” is selectiveprogressive in political pluralism but conservative in gender issues thereby reinforcing patriarchal structures under the guise of neutrality. The research calls for methodological transparency, inclusion of female scholars in translation teams, and a plural translation system that accommodates feminist perspectives to achieve epistemic justice in Qur’anic translation in Indonesia